(untitled) (Global Journal of Science Frontier Research, 2013)
Field equations in the presence of wet dark fluid are obtained in Saez-Ballester theory using Bianchi type-I space-time. A new equation of state for the dark energy component of the Universe has been used. It is modeled on the equation of state which can describe a liquid for example water. The exact solutions are obtained in quadrature form. The solution for both power-law and exponential forms are studied. The physical and geometrical properties of the model are also studied.